Laminins affect T cell trafficking and allograft fate - Kristi J. Warren; Daiki Iwami; Donald G. Harris; Jonathan S. Bromberg; Bryna E. Burrell (The Journal of Clinical Investigation, 2014)
Lymph nodes (LNs) are integral sites for the generation of immune tolerance, migration of CD4+ T cells, and induction of Tregs. Despite the importance of LNs in regulation of inflammatory responses, the LN-specific factors that regulate T cell migration and the precise LN structural domains in which differentiation occurs remain undefined. Using intravital and fluorescent microscopy, we found that alloreactive T cells traffic distinctly into the tolerant LN and colocalize in exclusive regions with alloantigen-presenting cells, a process required for Treg induction. Extracellular matrix proteins, including those of the laminin family, formed regions within the LN that were permissive for colocalization of alloantigen-presenting cells, alloreactive T cells, and Tregs. We identified unique expression patterns of laminin proteins in high endothelial venule basement membranes and the cortical ridge that correlated with alloantigen-specific immunity or immune tolerance. The ratio of laminin α4 to laminin α5 was greater in domains within tolerant LNs, compared with immune LNs, and blocking laminin α4 function or inducing laminin α5 overexpression disrupted T cell and DC localization and transmigration through tolerant LNs. Furthermore, reducing α4 laminin circumvented tolerance induction and induced cardiac allograft inflammation and rejection in murine models. This work identifies laminins as potential targets for immune modulation.